Acremonium variecolor strain 130360 VS Trichoderma harzianum STRAIN MGQ2 IN BIOCONTROL: AN OVERVIEW OF FUNGAL ANTAGONIST APPLIED AGAINST FUNGAL PATHOGEN Fusarium oxysporum, A CAUSE OF MOLER’S DISEASE IN SHALLOT - Gunawan Sutio; Rani Maharani; Nur Afifah Azzahra (BIOVALENTIA: Biological Research Journal, 2022)
One  of  the  common  diseases  of  shallot  is  moler  disease,  caused by Fusarium oxysporum. This disease causes some damage to the plant. The attack mechanism of Fusarium oxysporum is by penetrating, colonizing, and multiplying in the root area, then parasitizing and inhibiting  the  process of  carrying  water  to  whole  parts  of  the  plant. Biological   control   of   moler   diseases   using   fungal   antagonist   has developed considerably in recent years. Fungal antagonists play a significant role in controlling plant pathogens and moler diseases caused by Fusarium oxysporum, such as Trichoderma harzianum and Acremonium variecolor. A series of experiments in field conducted to assess the comparison of ability between Trichoderma harzianum strain MGQ2   and   Acremonium   variecolor   strain   130360   in   effectively controling moler in shallot.